2014
DOI: 10.1117/1.jbo.19.8.085004
|View full text |Cite
|
Sign up to set email alerts
|

Additivity of light-scattering patterns of aggregated biological particles

Abstract: The paper is focused on light scattering by aggregates of optically soft particles with a size larger than the wavelength, in particular, blood platelets. We conducted a systematic simulation of light scattering by dimers and larger aggregates of blood platelets, each modeled as oblate spheroids, using the discrete dipole approximation. Two-dimensional (2-D) light scattering patterns (LSPs) and internal fields showed that the multiple scattering between constituent particles can be neglected. Additionally, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…Many different features of the cell, such as statistical variation in size and shape [clearly evident in Fig. 3(a)] and absorption, as well as correlations between the individual component's scattering distributions, 22,23 can cause variations in the final measurement. Therefore, the relative concentration of each cell component is more relevant for determining cell viability.…”
Section: Resultsmentioning
confidence: 99%
“…Many different features of the cell, such as statistical variation in size and shape [clearly evident in Fig. 3(a)] and absorption, as well as correlations between the individual component's scattering distributions, 22,23 can cause variations in the final measurement. Therefore, the relative concentration of each cell component is more relevant for determining cell viability.…”
Section: Resultsmentioning
confidence: 99%
“…In Fig 8B , the intensity of scattered light (more precisely, the Mueller matrix element S 11 ) is shown as a function of polar and azimuthal scattering angles. The distribution of intensity shows complex features and is distinctive from smooth pattern of oblate spheroid described in [ 66 ]. Note also that the presented model of activated platelet not only possess one or two additional morphological parameter in comparison with models of resting platelets, but also lacks axial symmetry, which brings about the influence of Euler angle γ on the light-scattering patterns.…”
Section: Methodsmentioning
confidence: 94%
“…Moskalensky et al. [ 167 ] showed that multiple scattering of the optically soft monomers inside an aggregate can often be neglected.…”
Section: Characterization Methods and Inverse Problemsmentioning
confidence: 99%